Graphene-embedded carbon nanofibers decorated with Pt nanoneedles for high efficiency dye-sensitized solar cells. Issue 34 (14th September 2015) - Elbohy, Hytham; Aboagye, Alex; Sigdel, Sudhan; Wang, Qi; Sayyad, M. Hassan; Zhang, Lifeng; Qiao, Qiquan
<x xml:space="preserve">Abstract</x> Graphene-embedded carbon nanofibers (GCNFs) were developed as a new counter electrode nanomaterial for high efficiency dye-sensitized solar cells (DSCs).